ANALISIS LALU LINTAS AKIBAT PEMBANGUNAN JALAN LAYANG CAKUNG CILINCING TANJUNG PRIOK JAKARTA - Intan Fitriani; Ratna Manik Pratiwi; Wahyudi Kushardjoko; YI. Wicaksono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Cakung-Cilincing Highway is the main access road to the Tanjung Priok port. The flyover is being built on the road. This causes severe congestion. This study aimed to compare the capacity, the current movement, vehicle speed, and vehicle operating costs at the time before the construction of flyover and during construction of elevated road. Analysis using Manual Kapasitas Jalan Indonesia and Synchro SimTraffic 7.0 program to simulate passing vehicles. The results show the capacity before and during construction is the same, namely 5152,8 pcu/hour because the contractor was to minimize the possibility of harm to road users. Current movement to port more dominant either before or during construction indicated by the greater density toward Priok compared to the Cakung and speed toward Priok lower compared to the Cakung. Traffic density prior to the construction of the port of Tanjung Priok 166 vehicles/km and the direction Cakung of 98 vehicles/km. While the current construction of 229 Priok towards vehicle/km and 143 vehicles/km toward Cakung. The average speed of the vehicle prior to the construction Priok is 41,22 km/h and the direction Cakung 42,26 km/h. While the construction time of 4,86 km/h in the direction Priok and the direction Cakung 8.41 km/h. This is because the construction of the overpass project activities Cakung Cilincing and potholes. Total vehicle operating costs incurred prior to construction lower than at the construction details before construction towards Priok is Rp 679,485,269.47 / day / 1.8 km and to the Cakung Rp 492,487,489.56 / day / 1.8 miles. While the current construction towards Priok Rp 1,014,197,666.44/day/1,8 km and to the Cakung Rp 529,568,278.05/day/1,8 km. This is caused by the increased density of the way so the speed decrease and result in greater costs. Therefore, should the perforated Cakung Cilincing immediately improved and widening of roads so as to improve the speed of vehicles passing through the road.